Thermal Benthic Diatom from Panchor Hot Spring in Serian, Sarawak - Izni Arifah, bt Shuib (Universiti Malaysia Sarawak (UNIMAS), 2014)
This study was aimed to determine the thermal benthic diatom genera of Panchor Hot Spring in Serian, Sarawak. Diatoms were sampled from three types of substrates that were macroalage, leaves, and woods. There were seven genera of diatoms including one unidentified genus recorded during this study. Diatoms genera for every sampling months were almost the same and generally can be found on every type of substrates. Dominating genera were Navicula, Gomphonema and the Unidentified genus. Substrates of macroalage and leaves recorded the highest number of individual diatoms compared to the woods. Most of the diatoms genera had no significant correlation with physico-chemical parameters.